HUBUNGAN KARAKTERISTIK IBU DAN PERKEMBANGAN EMOSIONAL ANAK USIA 3-5 TAHUN DI WILAYAH KERJA PUSKESMAS SUMBER KABUPATEN CIREBON - Yosi Yusrotul Khasanah; Ika Choirin Nisa; Siti Nurdiyana; Heny Puspasari; Agi Yulia Ria Dini; Susilawati (Jurnal Medicare, 2026)
The golden period (golden age) is a sensitive period of growth and development that only occurs once in a lifetime. Broadly speaking, the domain of child development consists of gross motor skills, fine motor skills, language/speech, and personal social/independence.The aim of the research was to determine the relationship between maternal characteristics and the emotional development of children aged 3-5 years in the Sumber Health Center Working Area, Cirebon Regency. The research method is quantitative research with a correlational study design approach. The research was conducted in the Sumber Health Center Working Area, Cirebon Regency, on 40 mothers who had children aged 3 - 5 years. The analysis used is the chi square test between the independent variable and the dependent variable. The research results show that the majority of respondents are 26-35 years old (60.00%), the majority of respondents have moderate education (67.50%), the majority of respondents do not work (62.50%) and the majority of children aged 3-5 years grow according to development. as many as 33 people (82.50%). The chi square test results showed that there was a relationship between maternal age and education and the emotional development of children aged 3-5 years with a p value= 0.007 and 0.003. This research recommends that interested parties pay more intense attention to children who are indicated to have abnormal emotional development problems, so that they can help parents in providing good care as an effort to improve children's behavior.         The research method is quantitative research with a correlational study design approach. The research was conducted in the Sumber Health Center Working Area, Cirebon Regency, on 40 mothers who had children aged 3 - 5 years. The analysis used is the chi square test between the independent variable and the dependent variable. The research results show that the majority of respondents are 26-35 years old (60.00%), the majority of respondents have moderate education (67.50%), the majority of respondents do not work (62.50%) and the majority of children aged 3-5 years grow according to development. as many as 33 people (82.50%). The chi square test results showed that there was a relationship between maternal age and education and the emotional development of children aged 3-5 years with a p value= 0.007 and 0.003. This research recommends that interested parties pay more intense attention to children who are indicated to have abnormal emotional development problems, so that they can help parents in providing good care as an effort to improve children's behavior.